Head rotation and illusory force sensation by lateral skin stretch on the face - Miyakami, Masahiro; Takahashi, Akifumi; Kajimoto, Hiroyuki (Frontiers in Virtual Reality, 2022)
Various methods for inducing an illusory force sensation to present a sense of force to users in energy-saving and space-saving systems have been proposed. One of them is the illusion of force sensation induced by cutaneous sensory stimulation. In this study, we hypothesized and empirically verified that lateral skin stretch alone on the face can induce an illusory force sensation in the direction of the stretch. We focused on the anterior temporal and cheekbone regions, in which the cushion part of the head-mounted display contacts the skin, and applied skin stretches of different intensities to these regions, envisioning a force presentation device built into the head-mounted display. Head rotations of approximately 40 and 50 degrees were generated by skin stretches in the anterior temporal and cheekbone regions, respectively, confirming the illusory force sensation in the direction of rotation. We confirmed a positive correlation between the head-turning angle and the amount of skin deformation. The intensity of the illusory force sensation can be controlled by changing the amount of lateral skin deformation; this may be applied to the development of a new force presentation head-mounted device.